Assessment of soil fertility in relation to dragon fruit (Hylocereus costaricensis) cultivation in south-eastern region of Bangladesh (Journal of Biodiversity Conservation and Bioresource Management, 2025)
Soil, shoot and fruit samples were collected from twenty Dragon (Hylocereus costaricensis) orchards under different locations of Cumilla to evaluate some physico-chemical properties and nutrient status. The pH of the soil varied from medium acidic to slightly alkaline (4.8 to 7.7), organic matter content varied from 1.01 to 1.95%, EC varied from 0.11 to 0.55 mS/cm. The dominant soil textural classes were loam and silt loam. The total and available N, P, K and S in soils were found to be 0.085 to 0.203% and 24.54 to 38.70 ppm, 0.027 to 0.185% and 12.74 to 76.44 ppm, 0.021 to 0.119% and 12.40 to 42.70 ppm, 0.096 to 0.213% and 9.4 to 34.8 ppm, respectively. The total N, P, K and S concentrations in shoots of dragon were 3.08 to 4.24, 0.102 to 0.246, 0.110 to 2.870 and 0.073 to 1.122%, respectively. Nutrients such as protein, N, P, K, Ca and Mg found in fruit varied from 10.20 to 17.80, 1.632 to 2.848, 0.071 to 0.184, 0.104 to 3.548, 0.057 to 0.135% and 0.118 to 0.295%, respectively. This study reveals low to medium soil fertility under dragon fruit plantations in the Cumilla region, Bangladesh. Farmers are advised to apply soil amendments to improve soil physico-chemical properties prior to planting. Regular soil testing and tailored nutrient management are recommended to enhance fertility and productivity, promoting sustainable practices and improved economic returns.J. biodivers. conserv. bioresour. manag. 10(2), 2024: 87-98